Pashas and the Andean Cosmovision - Cuba Manrique, María del Carmen (2018)
This article shows, in the first place, a legendary event: the foundation of Pashas propitiated by the union of the «prince» of Mashgonga and the «princess» of Llactabamba and, second, a ritual happening: the celebration of the feast patron saint of the Virgin of Llactabamba, with the participation of Cabanenses (symbolically Pashas) and llactabambinos. The archaeological footprints and rituals of this area show certain cultural and linguistic features of culle society, which, despite the invasion of Quechua society, first and Hispanic society, later; it survives in this area. The texts analyzed have been collected in oral and written language. In them, apart from contemplating the dialectal Castilian, there are features of the Andean worldview, which is more clearly recorded in the variants of the legend, while in the current ritual, syncretic forms or substitutions of Andean religious thought by the Christian.